RANCANG BANGUN APLIKASI PEMBELAJARAN UNTUK ANAK USIA DINI BERBASIS ANDROID - Kurniawan, Kurniawan; Sahfitri, Vivi (Universitas Bina Darma, 2016)
Abstract: Education is spearheading the human form smart and competitive so as to produce qualified human resources and able to compete. A good education should start from an early age. With proper education, will be able to produce children who have the intellectual quality. The exact method can provide a good mindset for children early age so that they can stimulate their memories which can also be a solid foundation in the process of intellectual development of children. The existence of the current smartphone makes it easy for children to learn. This study aimed to establish a learning application for android-based early childhood. System development method used is the Waterfall model. Applications built is expected to help the children an early age to learn both to recognize numbers, recognize letters, recognize words and counting. Keywords: Smartphone, Application of Learning, Android, Early Childhood